Implementation of Kemuhammadiyahan Al-Islam Learning System at Nurul Hadina Junior High School - Reza Pahlawan Asri; Rahmadani Syahfitri (UMSU, 2023)
This research aims to find out Implementation of Kemuhammadiyahan Al-Islam Learning System at Nurul Hadina Junior High School. This type of research is where the researcher determines the best problem or question for participants or resource persons later. In this approach, researchers need. which is the location of this research in the city of Medan, precisely at SMP Nurul Hadina Medan Amplas. The learning system which is the object of research while the research subject itself is the Al-Islam Kemuhammadiyahan subject. This research was conducted within two months. For about two months the researcher carried out his task of analyzing the Al-Islam Muhammadiyah learning system at Nurul Hadina Middle School. The more data obtained, the better the final results of a study. In this study, data collection techniques were carried out by utilizing several techniques, including observation, interviews, documentation Based on the results of observations at Nurul Hadina Middle School, researchers found that students at Nurul Hadina Middle School are also people who need to be guided, directed and mentored at school to become quality human resources in the future regardless of status, race, race. ethnicity, difference. skin especially, with differences in economics and school locations. Students in cities, especially SMP Nurul Hadina also need to get moral education which must be added in order to improve good social behavior with a little extra handling because students there lack motivation, interest in learning and reading still need to be improved and want to raise more awareness to really seek highest knowledge